Sustainability Assessment of Hydrogen Production Techniques in Brazil: A Multi-criteria Analysis - Tapia, Luis Carlos Félix; Vigouroux, Rolando Zanzi; Silveira, José Luz [UNESP] (Springer Nature, 2017)
Current global demands for energy resources along with the continuous global population growth have created a great deal of stress among natural environments and societies in fulfilling such a need without disrupting economic and social structures. Policy- and decision-making processes hold some of the most important keys to allow safe paths for societies towards energy security and to safeguard the environment. Brazil has played a leading role in renewable energy production and use during the last few decades, thus becoming one of the world’s leading producers of sugarcane-based ethanol, and adapted policies to support renewable energy generation and use. Although it is true that Brazil has historic experience in managing renewables development and their further integration into the consumer market, there is still a lot to be done in order to drive new technologies that could reduce emissions even further, thus increasing economic stability and social welfare.